Analysis of the effect of third party fund, capital adequacy ratio, and loan to deposit ratio on bank‟s profitability after the application of IFRS - You Are Nita Sari; Nur Suci I Mei Murni (The Indonesian Accounting Review, 2016)
The objective of this research is to analyze the effect of third party fund, capital adequacy ratio, and loan to deposit ratio on bank’s profitability after the application of IFRS. The bank’s profitability in this study is measured using return on assets (ROA). The samples used are 22 conventional commercial banking companies listed on the Indonesia Stock Exchange in the period from 2012 to 2013, which are selected through purposive sam-pling method. The analysis technique used is multiple linear regression analysis. The results of this study indicate that: (1) the variables of third party funds (TPF), capital adequacy ratio (CAR), and loan to deposit ratio (LDR) simultaneously have significant effect on return on assets (ROA); (2) the variable of third party fund (TPF) partially has positive but not significant effect on return on assets (ROA); (3) the variable of capital adequacy ratio (CAR) partially has positive and significant effect on return on assets (ROA); (4) the variable of loan to deposit ratio (LDR) partially has positive but not sig-nificant effect on return on assets (ROA) in conventional commercial banking companies listed on the Indonesia Stock Exchange (after the implementation of IFRS. The ability of the independent variables to explain the dependent variable in this study is 17.8%, while the remaining 82.2% is explained by other variables outside the models studied.